6ER-031 Development of a patient centred video on medication management and a qualitative exploration of patients' opinions towards the video. (14th March 2021) - Dillon, L; Kieran, M; Brown, J
Abstract : Background and importance: Insufficient patient knowledge of medicines on discharge from hospital can increase the risk of a medication related problem, which in turn can result in an adverse drug event occurring. Adverse drug events are a prominent factor of hospital readmissions which in turn increase illness and healthcare costs. There is no global standardised process for educating patients on how to manage their medicines on discharge from hospital. Aim and objectives: The aim of this study was to describe the development of a video to educate patients on medication management on discharge from hospital. In the process of developing the video, discharged patients' opinions of the video were explored with the objective of increasing the quality and usability of the tool. Material and methods: The video was designed and developed by a project team which consisted of various hospital staff members. A selection of patients who attended the hospital cardiac rehabilitation outpatient service (CROS) were purposefully sampled to watch the video and to complete a face-to-face semi-structured interview to determine their opinions towards the video. The semi-structured interviews were audio recorded, transcribed precisely and analysed using an inductive thematic approach. Results: The video was 6 min and 29 s in duration and was designed around the theory of multimedia learning and the application of video design principles. Ten patients from the hospital CROS viewed the video and completed a semi-structured interview on their opinions towards the video. Patients ranged in age from 41 to 81 years (mean 60 years) and were predominantly men. Three major themes and several subthemes were identified in relation to patients' opinions of the video: theme 1=patient education; theme 2=accessibility; and theme 3=enhancing patient empowerment. Conclusion and relevance: This study illustrated the development of an educational video on medication management and the potential of the video to empower patients and enhance learning. All interviewees concluded that the video should be incorporated into the hospital discharge process and suggestions on how to improve access and patient learning from the video were reviewed. The video is now live on the hospital website. References and/or acknowledgements: Conflict of interest: No conflict of interest